STUDENTS’ PERCEPTIONS OF EFFECTIVE LECTURER TEACHING - Mohamad Kamil Ariff Khalid; Normala Ismail (Journal of Islamic, Social, Economics and Development, 2020)
Lecturers play an important role in education, teaching and learning processes. Theprocess of teaching and learning involves the interaction between students and lecturers. Thepurpose of this study is to examine the students’ perspective on the effectiveness of lecturers’teaching. The sample consists of 300 Diploma students from various faculties who study atUniversiti Teknologi MARA (UiTM) Pahang, Raub Campus. The instrument was aquestionnaire distributed to the respondents using stratified random sampling. The data wasanalysed using the Statistical Package for Social Sciences (SPSS) version 23. This study foundthat the effectiveness of lecturers’ teaching can be seen from the aspect of personality, teachingbehaviour, relationship and attitude of lecturers towards students. The findings also show thatthere are five main characteristics in the lecturers’ personality which are of students’ choice;friendly, firm, caring, punctual and diligent. The Multiple Regression Analysis results showthat the lecturers’ knowledge and teaching experience are the dominant factors that influencethe students’ grades. Furthermore, this study did not deny that the lecturers’ personality whoare friendly, easily approachable and loves to joke are also significant estimators for theiracademic achievement. The researcher hopes through this study lecturers can diversify theirefforts so that the teaching and learning process can be smooth and fun to attract students tostrive for their best.